THE STRATEGY OF UNILEVER'S CORPORATE SOCIAL RESPONSIBILITY 6.0 IN BUILDING CORPORATE PERSONAL BRANDING - Kusuma, Ema; Barus, Imelda; Pranawukir, Iswahyu (Moestopo International Review on Social, Humanities, and Sciences, 2024)
The aim of the research is to find out the Corporate Social Responsibility (CSR) 6.0 strategy implemented by the Unilever company in building corporate personal branding. The research approach uses descriptive qualitative with a case study method to describe how Unilever is committed to CSR 6.0 and how this impacts the company's image. The data consists of documentation studies, including: Unilever's sustainability reports, company publications and related articles and research, followed by observations. The research results show that the CSR 6.0 concept is the substance of communication management carried out by Unilever in building personal branding. In fact, the CSR 6.0 concept has had an impact on Unilever's strong corporate personal branding. As for the implementation of communication, the CSR 6.0 strategy is the content of a sympathetic communication management message that Unilever has seven pillars of CSR 6.0 targets: 1) Health and Welfare, 2) Environmental Impact Reduction, 3) Social Inclusion, 4) Empowerment of Farmers and Ranchers, 5) Protection Human Rights, 6) Food and Nutrition Security, 7) Community Engagement.